Computational fluid dynamic analysis of temperature distribution on the integrated pyrolysis–fractionation process of used oil - Maya Ramadianti Musadi; Etih Hartati; Sofia Umaroh; Adinda Azzahra Dwi Maharani; Senna Joseph Yogaswara; Faza Rosada; Siti Salma Humaidah (Results in Engineering)
Used oil, particularly from motor vehicles and industrial machinery, is composed of several harmful contaminants capable of causing serious risks to the environment and human health. This shows the need for proper management that complies with the government rules. When used oil is dumped into the soil, it penetrates and contaminates the groundwater, thereby disturbing the balance of the ecosystem. Disposal into rivers, lakes, or seas, also leads to the formation of a thin layer on water surface that interferes with the oxygenation, killing fish and other aquatic organisms. Handling used oil by burning is highly prohibited because inhaling the vapor can cause respiratory problems. Additionally, there are carcinogenic compounds such as PAHs that have the potential to cause cancer in humans over a long period of time. Despite the numerous disadvantages, used oil has the potential to be converted into several liquid fuels with similar chemical and physical properties to petroleum products. To obtain liquid fuels from used oil, integrated pyrolysis-fractionation method is often applied, consisting of pyrolysis reactor and a fractionation column. Pyrolysis reactor has a diameter of 0.60 m and a height of 0.50 m with three thermocouples placed from the bottom to the top. The fractionation column has a diameter of 0.60 m and a height of 1.5 m with five thermocouples placed from the bottom to the top. Therefore, this study aimed to evaluate temperature distribution in the fractionation column of integrated pyrolysis-fractionation system of used oil, providing a basis for potential scale-up. The experiment and simulation results showed that temperature distribution in the fractionation column could be analyzed through computational fluid dynamics (CFD). The average temperature was observed to decrease in the fractionation column from the bottom to the top. For the experiment, average column temperature decreased from 267 °C (bottom) to 40 °C (top). Meanwhile, in the simulation, average column temperature decreased from 267 °C (bottom) to 51 °C (top). This study showed the model's ability to forecast temperature distribution in the fractionation column, as indicated by the slight discrepancy between experiment and CFD simulation results.